Hormone and carbohydrate metabolism associated genes play important roles in rhizome bud full‐year germination of Cephalostachyum pingbianense. Issue 2 (5th April 2022) - Li, Lushuang; Xia, Tize; Li, Bin; Yang, Hanqi
Abstract: Cephalostachyum pingbianense is the only woody bamboo species that can produce bamboo shoots in four seasons under natural conditions. So far, the regulatory mechanism of shoot bud differentiation and development is unknown. In the present study, indole‐3‐acetic acid (IAA), zeatin riboside (ZR), gibberellin A3 (GA3 ) and abscisic acid (ABA) contents determination, RNA sequencing and differentially expressed gene analysis were performed on dormant rhizome bud (DR), growing rhizome bud (GR), and germinative bud (GB) in each season. The results showed that the contents of IAA and ZR increased while ABA content decreased, and GA3 content was stable during bud transition from dormancy to germination in each season. Moreover, rhizome bud germination was cooperatively regulated by multiple pathways such as carbohydrate metabolism, hormone signal transduction, cell wall biogenesis, temperature response, and water transport. The inferred hub genes among these candidates were identified by protein–protein interaction network analyses, most of which were involved in hormone and carbohydrate metabolism, such as HK and BGLU4 in spring, IDH and GH3 in winter, GPI and talA / talB in summer and autumn. It is speculated that dynamic phytohormone changes and differential expression of these genes promote the release of rhizome bud dormancy and contribute to the phenological characteristics of full‐year shooting. Moreover, the rhizome buds of C. pingbianense may not suffer from ecodormancy in winter. These findings would help accumulate knowledge on shooting mechanisms in woody bamboos and provide a physiological insight into germplasm conservation and forest management of C. pingbianense .